(PtBA-co-PPEGMEMA-co-PDOMA)-g-PPFA polymer brushes synthesized by sequential RAFT polymerization and ATRP. Issue 20 (30th April 2018) - Shen, Dingfeng; Xu, Binbin; Huang, Xiaoyu; Zhuang, Qixin; Lin, Shaoliang
Abstract : This article reports the synthesis of semi-fluorinated (P t BA- co -PPEGMEMA- co -PDOMA)- g -PPFA polymer brushes for self-cleaning anti-fouling surfaces. Abstract : A novel approach for preparing self-cleaning anti-fouling surfaces with compositional heterogeneous polymer brushes at a molecular-length scale was developed. This approach exploits three critical elements including hydrophilic poly(ethylene glycol) (PEG) brushes with non-fouling functionalities, self-cleaning fouling-release hydrophobic poly(2, 2, 3, 3, 3-pentafluoropropyl acrylate) (PPFA) brushes and catechol moieties, an important component of mussel adhesive proteins (MAPs), to anchor asymmetric polymer brushes onto surfaces. Well-defined P t BBPMA- co -PPEGMEMA- co -PDOMA macroinitiators were first prepared by RAFT copolymerization of tert -butyl 2-((2-bromopropanoyloxy)methyl)acrylate ( t BBPMA) bearing a Br-containing ATRP initiating group, poly(ethylene glycol) methyl ether methacrylate (PEGMEMA) macromonomer and N -(3, 4-dihydroxy-phenethyl) methacrylamide (DOMA) with an adhesive anchoring group of catechol moieties. The target asymmetric polymer brushes were obtained by ATRP of PFA initiated by the macroinitiator via the grafting-from strategy. By using the drop coating method, the asymmetric polymer brush surface could form a layer of amphiphilic brushes onto the substrate with the assistance of adhesive anchoring groups. With a dense heterogeneous brush conformation at a molecular-length scale, (P t BA- co -PPEGMEMA- co -PDOMA)- g -PPFA-based surface shows considerable self-cleaning anti-fouling performance with less protein adsorption (up to 93% off) and cell adhesion (up to 88% off) compared to the bare surface.